PENGARUH PENDIDIKAN KEWIRAUSAHAAN, PENGALAMAN BERWIRAUSAHA, DAN JENIS KELAMIN TERHADAP SIKAP BERWIRAUSAHA PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS MUHAMMADIYAH SURABAYA - Wahyudiono, Andhika (UNIVERSITAS NEGERI SURABAYA, 2016)
This study aims to determine the effect of entrepreneurship education, entrepreneurship experience, and gender of the entrepreneurship attitude either partially or simultaneously. The population in this study were students S1 class of 2012 and 2013 the Faculty of Economics, University of Muhammadiyah Surabaya consists of two majors, namely accounting and management which all are 206 students with a sample of 103 people. The data collection techniques used were questionnaires, interviews, and documentation. The method of analysis used multiple linear regression analysis. The results showed that entrepreneurship education, entrepreneurship experience, and the gender type have significant effect on the attitude of berwirusaha either partially or simultaneously